Integrating Accountability, Governance, And Legal Risk: Lessons Learned From The Efishery Business Model - Afriansyah Tanjung; Agniya Thahira; Farinza Tiara Indani; Moh Lubsi Tuqo Romadhan (Jurnal Pengabdian Masyarakat, 2026)
Purpose: This paper aims to explicitly analyze the complex challenges of accountability, corporate governance, and legal risk faced by the Indonesian agritech unicorn, eFishery, as it manages rapid growth. The study addresses critical issues like alleged financial fraud, miscommunication, and resulting trust deficits, highlighting the imperative for transparent and accountable management to ensure sustainable growth in the agritech sector. Method: The research employs a descriptive qualitative approach with a case study design. Data was collected from secondary sources, including primary legal materials (e.g., Civil Code, UU ITE, OJK regulations) and secondary legal materials (e.g., journal articles, media reports). Content analysis with a thematic focus on accountability, governance, and legal risk was used for data analysis. Practical Applications: The findings offer crucial lessons learned and policy recommendations for other technology-based startups in Indonesia and the wider startup ecosystem. It emphasizes the practical steps of strengthening governance structures, enhancing transparency, and implementing robust internal oversight to build legally compliant and sustainable business models. Conclusion: The study concludes that integrating accountability and transparency from the early stages of growth and implementing Good Corporate Governance (GCG) are key to mitigating risks and ensuring eFishery's long-term sustainability. Governance failures, including ineffective oversight and a less assertive Board of Commissioners, must be addressed to maintain integrity and stakeholder trust.